Effective personal communication skills for public relations - Green, Andy (Kogan Page, 2006)
Make ideas contagious through every channel of communication. Viral marketing -- word-of-mouth marketing that spreads rapidly -- is now mainstream, but some of its concepts are still catching on in the realm of public relations. Drawing partly on the theories of evolutionary biologist Richard Dawkins, who used the phrase "meme" to describe a self-replicating unit of cultural information, Andy Green shows how contagious ideas --or memes -- can spread through PR communications like a virus. This stimulating, original book shows how to harness the power of communication to send out a message not just virally, but through online traditional channels as well.